PENDEKATAN INTERDISIPLINER SEBAGAI PARADIGMA BARU DALAM PENDIDIKAN DASAR - Nurul Hikmah; Syofiani; Nurul Fadli; Halimah; Rieke Alyusfitri (STKIP Subang, 2026)
This article examines the interdisciplinary approach as a new paradigm in basic education, which is considered relevant in responding to the complexity of 21st-century challenges. The rapid development of science, technology, and social change requires students not only to master knowledge in a partial and fragmented manner, but also to be able to integrate various concepts to understand and solve real-life problems. However, learning practices in elementary schools are still dominated by traditional, subject-based models that are fragmented by disciplines. This pattern causes knowledge to be learned separately, making it difficult for students to connect concepts and apply them in their daily lives.The interdisciplinary approach emerges as an alternative learning paradigm that emphasizes the integration of different disciplines within a unified learning experience. Through this approach, students are guided to study a theme or problem from multiple perspectives, making learning more meaningful, contextual, and holistic. Furthermore, this approach is believed to foster 21st-century competencies such as critical thinking, creativity, collaboration, communication, and integrated problem-solving skills.This study aims to examine in depth the conceptual foundations of the interdisciplinary approach, identify the problems of basic education that remain fragmented, and analyze the relevance of the interdisciplinary approach as a new paradigm in the learning process. The method used is a qualitative descriptive approach through a literature review of educational theories, curriculum policies, and previous studies related to integrated and interdisciplinary learning in basic education.The findings indicate that the interdisciplinary approach is able to create more meaningful learning, integrate various disciplines, and connect the learning process with students’ real-life contexts. Learning becomes more active, reflective, and problem-oriented. However, its implementation still faces several challenges, including limited teacher understanding and readiness, curriculum structures that remain subject-centered, and assessment systems that emphasize cognitive outcomes. Therefore, systemic support, paradigm shifts, and supportive policies are required so that the interdisciplinary approach can be implemented effectively in basic education.